PENGARUH LATIHAN LOMPAT TALI DENGAN CEPAT TERHADAP KECEPATAN LARI 30 METER ATLET PUTRA CLUB TENISMEJA MALAY PEKANBARU RIAU - M.Al Muhassyiby; Ramadi Ramadi; Zainur Zainur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know if there is any influence of jump rope practice quickly to the speed of running 30 meter on malay table tennis team Malay Pekanbaru Riau. The type of research used is experimental and using one-preetest-posttest design research group. The population in this research is on malay table tennis team Malay Pekanbaru Riau, amounting to 6 people. The sample technique used is total sampling (saturated samples), where all the population is sampled. Thus the sample in this study amounted to 6 people samples of men's table tennis team Malay Pekanbaru Riau. The instrument used is a 30 meter Running Test. After that, the data were processed by statistics, to test the normality by lilifors test at a significant level of α (0.05). The hypothesis that is proposed is the effect of fast jump training on the speed of running 30 meters on the men's table tennis team Malay Pekanbaru Riau. Based on the results of the analysis, there is average pree test 6.50 and post test 6.01 there is an average increase of 0.49 with t test that t arithmetic = 3.3> of t table = 1.943 Means t arithmetic> t table . Thus the effect of fast jump training on the speed of running 30 meters on the men's table tennis team Malay Pekanbaru Riau.Keywords: Jump Rope Quickly, Speed run 30 meters